Thermal Protective Properties of Aerogel-coated Kevlar Woven Fabrics (Journal of Fiber Bioengineering and Informatics, 2019)
In this work, silica aerogels were incorporated with high-performance Kevlar fabrics by coating to dealwith heat transfer problems under a severe environment. Thermal protective properties of the preparedfabrics were evaluated by using a laser system coupled with a thermometer which records the back-surfacetemperature of the fabric under laser radiation. The effect of aerogel content as well as pixel time usedfor laser radiation on thermal protection was investigated and discussed. Meanwhile, thermal propertiesof the fabrics under ambient temperature were tested with a thermal camera, thermal insulation valuesof the fabrics with different coatings were compared and analyzed. Moreover, fly ash nanoparticles wereused for coating as well to investigate their effect on thermal performance. The findings in this studycan be used for further research in aerogel-based high-performance materials for thermal protection.
Keywords: Kevlar; Aerogel; Thermal Protective Properties; Laser Radiation